Design optimization of oilfield subsea infrastructures with manifold placement and pipeline layout - Ramos Rosa, Vinícius; Camponogara, Eduardo; Martins Ferreira Filho, Virgílio José (Computers & chemical engineering, 2018)
•Pressure drop is modeled with multidimensional piecewise-linear approximation.•A simple but practical model that captures reservoir behavior in different conditions.•Fast model to carry out subsea layout case studies and perform sensitivity analysis. This paper presents a practical and effective optimization method to design subsea production networks, which accounts for the number of manifolds and platforms, their location, well assignment to these gathering systems, and pipeline diameter. It brings a fast solution that can be easily implemented as a tool for layout design optimization and simulation-based analysis. The proposed model comprises reservoir dynamics and multiphase flow, relying on multidimensional piecewise linearization to formulate the layout design problem as a MILP. Besides design validation, reservoir simulation serves the purpose of defining boundaries for optimization variables and parameters that characterize pressure decrease, reservoir dynamics and well production over time. Pressure drop in pipelines are modeled by piecewise-linear functions that approximate multiphase flow simulators. The resulting optimization model and approximation methodology were applied to a real oilfield with the aim of assessing their effectiveness.